Density functional theory study of α-Bromolauric acid adsorption on the α-quartz (1 0 1) surface. (June 2016) - Zhu, Yimin; Luo, Binbin; Sun, Chuanyao; Liu, Jie; Sun, Haitao; Li, Yanjun; Han, Yuexin
Graphical abstract: Highlights: Adsorption mechanism of α-BLA on quartz surface has been investigated based on DFT. Essential setting parameters convergence tests of quartz optimization were conducted. Convergence tests for an optimum quartz slab were conducted based on surface energy. Influences of H2 O and OH − on collecting property of α-BLA for quartz were studied. Activation mechanism of quartz by Ca(II) was studied by first-principle calculations. Abstract: Adsorption mechanism of collector α-Bromolauric acid (CH3 (CH2 )9 CHBrCOOH, α-BLA) on α-quartz (1 0 1) surface has been investigated by first-principles calculations based on density functional theory (DFT). The interaction energies of H2 O molecule, calcium ions (Ca 2+ ), hydroxyl ions (OH − ), calcium hydroxyl ions (Ca(OH) + ), and α-BLA − ions with α-quartz (1 0 1) surface were in the order of Ca(OH) + < Ca 2+ < OH − < H2 O < α-BLA − . The results revealed that the collector α-BLA cannot adsorb on α-quartz (1 0 1) surface due to the hindrance of hydration shell of quartz surface, while Ca(OH) + could repulse the hydration shell and consequently adsorb on quartz surface, which further leads to the adsorption of the collector α-BLA − anions on Ca(OH) + -activated quartz surface. Mulliken populations analysis of the external oxygen atom (O2) of quartz surface, calcium atom (Ca) of Ca(OH) +, and oxygen atom (O1) of collector α-BLA − (–OH group) shows that the electron transfer between the Ca–O1 and Ca–O2 atoms. The overlap area of electron density between Ca–O1 and Ca–O2 atoms indicates strong interactions among the three atoms of Ca, O1, and O2, suggesting that Ca(OH) + ions act as a bridge between the α-quartz (1 0 1) surface and the α-BLA collector.